ILLUSTRATION IN BOOKS AS MEANS EDUCATIONAL INFLUENCE ON CHILDREN - О. Pyvovarska (Academy of Cognitive and Natural Sciences, 2002)
The article is devoted to the educative influence of book illustrations on the child.